Pengaruh Penggunaan Aplikasi "Tentang Anak" Terhadap Pengetahuan, Sikap dan Perilaku Ibu dalam Memantau Status Gizi Baduta: Pengaruh Penggunaan Aplikasi "Tentang Anak” terhadap Pengetahuan, Sikap, dan Perilaku Ibu dalam Memantau Status Gizi Baduta - Sevin, Rhut; Humayrah, Wardina (Amerta Nutrition, 2024)
Background: In Indonesia, malnutrition among under-two children is currently still relatively high. On the other hand, many nutrition applications are available on smartphones. One of the popular applications used by mothers of under-two is "Tentang Anak", which makes it easy to monitor the children's nutritional status and growth. Objectives: This study aimed to analyze the effect of using the "Tentang Anak" application on mothers' knowledge, attitudes, and behavior in monitoring the nutritional status of under-two children. Methods: This study used a cross-sectional design. The data were collected purposively with self-administered questionnaires in the form of a validated Google Form. The data were collected using the official WhatsApp Group of the "Tentang Anak" user community, and 103 respondents of mothers of under-two in Indonesia were selected. The variables analyzed were socio-demographic characteristics, duration of application use, knowledge, attitudes, and behaviors about monitoring the nutritional status of under-two children. The simple linear regression test was used to measure the effect of application use on knowledge, attitudes, and behavior. Results: The scores of respondents' knowledge, attitudes, and behaviors regarding monitoring the nutritional status of under-two were above 75 (good category). The duration of use of all application features had a significant effect (p<0.05) on knowledge, attitudes, and behavior, although the strength of the relationship was weak (R2<0.33). The duration of use of the "growth" and "recipe" features also had a weak significant effect on knowledge and attitudes. The effect of the "ask an expert" feature was not analyzed because it was limited in answering user questions. Conclusions: "Tentang Anak" app could be a good literacy channel for users, reflected in the good knowledge, attitudes, and behavior scores. However, the duration of application use had a weak effect on improving knowledge and attitudes and had no significant effect on behavior.